Holocene vegetation dynamics and climatic fluctuations from Shuanghaizi Lake in the Hengduan Mountains, southwestern China - Trivedi, Anjali; Tang, Ye-Na; Qin, Feng; Farooqui, Anjum; Wortley, Alexandra H.; Wang, Yu-Fei; Blackmore, Stephen; Li, Cheng-Sen; Yao, Yi-Feng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2020)
The Hengduan Mountains of Southwest China are considered the most biologically diverse temperate ecosystem in the world. Here, we present a similar to 10,000-year pollen record from Shuanghaizi Lake, northwestern Yunnan, which we use to reconstruct vegetation dynamics, climatic fluctuations and variability in the Indian Summer Monsoon (ISM). The results suggest that, between 10,000 and 7900 cal. yr BP, vegetation comprised mainly mixed needle- and broad-leaved forest (mostly Abies, Pinus, Quercus, and Salix), indicating a warm and humid climate, corresponding to a strong ISM. From 7900 to 6900 cal. yr BP, the mixed needle- and broad-leaved forest persisted, while an increase in Abies pollen and decrease in pollen of Pinus and Salix implies a reduction in temperature and precipitation, suggesting a slightly weaker ISM than in the preceding phase. Between 6900 and 2400 cal. yr BP, an expansion of Pinus and Quercus in mixed needle- and broad-leaved forest, together with the first occurrence of the aquatic Potamogeton, suggest a warmer and more humid climate, likely due to the strengthening monsoon, consistent with the Holocene climatic optimum. From 2400 to 970 cal. yr BP, the vegetation shifted to needle-leaved forest with sparse patches of broad-leaved forest, concurrent with a weakening ISM through the middle of this period. During the first half of the period covering 970 to 470 cal. yr BP, Abies and Picea increased and we inferred the lowest temperature and precipitation of the whole study, implying the weakest ISM. In the middle of this period, an expansion of broad-leaved trees including Quercus, Alnus, Betula and Castanopsis plus diverse herbaceous plants suggests that the climate developed towards warmer and more humid conditions, in agreement with a gradual intensification of the ISM. After 470 cal. yr BP, the vegetation became dominated by needle-leaved forest and most broad-leaved elements became intermittent. Although the climate was generally cool and dry in this period, temperature and precipitation ...